AMENORRHEA AFTER CHEMOTHERAPY IN BREAST CANCER PATIENT - Ravi, Ramchandani; Haider, Ghulam; Ahmed, Khalil; Sami, Abdus; Zahoor, Saima; Lata, Ramchandani (Journal of Ayub Medical College Abbottabad, 2020)
Background: This study was conducted to determine the frequency of amenorrhea after chemotherapy among breast cancer patients. Methods: Total 201 premenopausal females (having menstruation during the past 6 months at the time of diagnosis) of age 15-45 years and had confirmed diagnosis of breast cancer requiring chemotherapy were included in the study using non-probability consecutive sampling technique. Amenorrhea within 6 months after the completion of chemotherapy was labelled as chemotherapy induced amenorrhea. Data was entered and analysed using SPSS-23. Results: The mean age of the patients was reported as 37.06±5.68 years. Majority of the females were married (86.6%) & multigravida (81.1%). Most of the patients (23.9%) received neoadjuvant chemotherapy followed by surgery and radiotherapy. A total of 129 patients received Adriamycin plus cyclophosphamide followed by paclitaxel as chemotherapy regimen. Out of 201 females, 184 (91.5%) experienced amenorrhea after start or completion of chemotherapy. Conclusion: The frequency of CIA was very high among breast cancer patients in our study, long term follow-up is needed to see input of CIA on future fertility. Keywords: Chemotherapy; amenorrhea; breast cancer; chemotherapy induced amenorrhea